PARENTING PATTERNS IMPACT ON CHILDREN’S SOCIAL INTELLIGENCE: STUDY ON PROGRAM KELUARGA HARAPAN BENEFICIARIES FAMILY - Eva Nursa'adah; Enceng Mulyana; Sri Nurhayati (Journal Of Educational Experts (JEE), 2022)
Parenting is a lifelong parenting process. This study aims to determine the impact of parenting style on children's social intelligence in beneficiary families. The research method used is qualitative. Data collection techniques used were interviews and documentation. Data analysis technique using the Mile and Huberman model consist of data reduction, data display, and conclusion. The research results obtained include (1) Several families have received assistance since 2015 (2) Assistance is carried outevery month with an average of 85% of participants from all residents due to business (3) 75% of parents apply democratic parenting and 25 % apply authoritarian parenting (4) Children need time to adapt in a new environment (5) children are able to share toys and food and (6) children are able to resolve disputes between friends without involving their parents.